2014
DOI: 10.1007/s10646-014-1312-9
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate-induced oxidative stress in isolated liver mitochondria

Abstract: As a new threat to environment all through the world, perchlorate (ClO4(-)) was predominantly a thyrotoxin, and its toxic manifestations in non-thyroid were also documented. To date, little is known about the effect of ClO4(-) on cell and organelle. To reveal the toxicity of ClO4(-) on living organism in-depth, mitochondria isolated from liver of Carassius auratus were incubated with different concentrations of ClO4(-). The results demonstrated that ClO4(-)-induced mitochondrial oxidative stress, and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Besides that, the increased oxidative stress has also been related to the augmented production of pro‐inflammatory cytokines and inflammatory status in the thyroid . In fact, perchlorate is a potent oxidizing agent, which has been previously associated with the induction of oxidative stress in different organisms . Moreover, a previous report suggested that this contaminant induces oxidative stress in the thyroid through the increased activity of the superoxide dismutase (SOD) and catalase (CAT) enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, the increased oxidative stress has also been related to the augmented production of pro‐inflammatory cytokines and inflammatory status in the thyroid . In fact, perchlorate is a potent oxidizing agent, which has been previously associated with the induction of oxidative stress in different organisms . Moreover, a previous report suggested that this contaminant induces oxidative stress in the thyroid through the increased activity of the superoxide dismutase (SOD) and catalase (CAT) enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, perchlorate was previously reported to inuence the mitochondrial metabolic activity and to even enhance the formation of Reactive Oxygen Species (ROS) in the mitochondria and increase the mitochondrial permeability transition pore (mPTP) openings in the goldsh Carassius auratus causing hepatocytes destruction. 48,49 The generated ROS were hypothesized to enhance DNA damage based on perchlorate induced DNA fragmentation in the isolated mitochondria. 50,51 Indeed, several antioxidant genes and oxidoreductases were enriched following perchlorate exposure in the nematodes.…”
Section: Microarray Qpcr Analysismentioning
confidence: 99%
“…[23][24][25][26][27] In addition, another in vitro study demonstrated that perchlorate could also induce oxidative stress in liver mitochondria, resulting in lipid peroxidative membrane damage. 22 In a population-based study using the NHANES data, Schreinemachers et al found a link between perchlorate exposure and indicators of oxidative stress and serum iron homeostasis. 49 Clearly, more studies are warranted to establish the pathogenic pathways linking perchlorate exposure and diabetes mellitus.…”
Section: Exposure Of Perchlorate Nitrate and Thiocyanatementioning
confidence: 99%
“…[13][14][15][16] Accumulating evidence has suggested that perchlorate, nitrate and thiocyanate could competitively inhibit thyroid iodine uptake and exert potential adverse effects on thyroid function, 6,[17][18][19] although some studies did not find such an association. 16,20,21 In addition, several in vivo and in vitro studies suggested that perchlorate exposure could induce oxidative stress in liver mitochondria, 22 and might also interfere with insulin secretion through affecting calcium channels. [23][24][25][26][27] Some studies suggested that dietary nitrate might have cardiovascular protective effects, 28,29 although its carcinogenic potential remained controversial.…”
Section: Introductionmentioning
confidence: 99%